Design of a FSS Bandpass Filter for C-Band Application with Equivalent Circuit Model - Khan, Mohd Salman (My University, 2019)
Frequency Selective Surface (FSS) configuration has been reported which behaves as a bandpass filter in C-band. The structure consists of a couple of metallic square loops designed over both sides of FR-4 dielectric as its unit cell. The proposed FSS band pass filter structure operates at centre frequency of about 6.74 GHz accompanied with –3dB working bandwidth (Δf) of about 3.3 GHz and -3dB Fractional Bandwidth (FBW) of 49.24 %. The simulation of the structure yields a -10 dB transmission bandwidth of 2.35 GHz ranging between 5.35 GHz and 7.7 GHz; yielding a fractional bandwidth of 35.7% with reflection coefficient achieving minima at 6.58 GHz. Furthermore, the transmission coefficient is close to unity over the aforementioned bandwidth. The surface currents and electric fields are studied, indicating the electromagnetic resonance to cause reflection dip.The Structural and Equivalent circuit configurations have been scrutinized and compared. The equivalent circuit model has –3dB working bandwidth of about 1.7 GHz operating about the centre frequency of 6.58 GHz and -3dB fractional bandwidth of 25.83 %. In spite of the fact that –3dB working bandwidth associated with the corresponding equivalent circuit configuration of the FSS BPF structure is tapered, yet still the requirement for bandwidth to be greater than 20 % is satisfied by the proposed lumped circuit model operating at center frequency of about 6.58 GHz and hence projected lumped circuit model of BPF is considered as wideband for C-band frequency applications. The proposed equivalent circuit model has been simulated and it has been found that the responses are in good resemblance.
Keywords: FSS; Band Pass Filter; Stop Band; Square loop Resonator(SLR)